양친의 대량 염기서열 해독을 통해 개발된 SNP 분자표지를 이용한 고추 유전자지도 작성 - 이준대(Jundae Lee); 박석진(Seok Jin Park); 도재왕(Jae Wahng Do); 한정헌(Jung-Heon Han); 최도일(Doil Choi); 윤재복(Jae Bok Yoon) (Weon'ye gwahag gi'sulji, 2013)
Molecular markers, as an efficient selection tool, have been and is being used for practical breeding program in chili pepper (Capsicum annuum L.). Recently, a lot of researches on inheritance and genetic analysis for quantitative traits including capsaicinoids, carotenoids, and sugar content in pepper are being performed worldwide. It has been also reported that QTL mapping is a necessary tool to develop molecular markers associated with the quantitative traits. In this study, we suggested a new method to construct a pepper genetic map using SNP (HRM) markers generated from NGS resequencing of female and male parents. Plant materials were C. annuum 'NB1' (female parent), C. chinense 'Jolokia' (male parent), and their $F_2$ population consisting of 94 progenies. Sequences of 4.6 Gbp and 6.2 Gbp were obtained from NGS resequencing of 'NB1' and 'Jolokia', respectively. Totally, 4.29 million SNPs between 'NB1' and 'Jolokia' were detected and the 1.76 million SNPs were clearly identified. Among them, total 145 SNP (HRM) primer pairs covering pepper genetic map were selected, and the 116 SNP (HRM) markers of them were located on this map. Total distance of the map, which consisted of 12 linkage groups and matched with basic chromosome numbers of pepper, was 1,167.9 cM. According to the mapping result, we concluded that our mapping method was suitable to construct a pepper genetic map fast and accurately. In addition, the genetic map could be directly used for QTL analysis of traits different between both parents. 효율적인 선발방법으로서 분자표지는 실제적인 고추(Capsicum annuum L.) 육종 과정에 사용되어 왔다. 최근에는 고추의 양적 형질로 알려진 매운맛, 색소 및 당 함량 등에 관한 다수의 유전분석 연구가 세계적으로 수행되고 있다. 또한 양적형질과 연관된 분자표지를 개발하기 위해서는 QTL mapping이 필수적이라고 보고되고 있다. 본 연구에서는 하나의 새로운 방법으로, 양친의 NGS resequencing을 통해 고추 유전자지도 상의 위치가 알려져 있는 분자표지를 일부 선발하여 SNP(HRM) 분자표지로 개발한 후 이를 이용하여 고추 유전체 전체를 포함하는 유전자지도 작성을 제안하고자 하였다. 식물재료는 C. annuum 'NB1'(모친)과 C. chinense 'Jolokia'(부친) 및 이들의 $F_2$ 세대 94개체를 사용하였다. 양친에 대해 NGS resequencing을 수행하여 각각 4.6Gbp와 6.2Gbp의 염기서열을 얻었다. 'NB1'과 'Jolokia' 간의 총 SNP 수는 429만개였으며, 그 중 확실한 SNP 수는 176만개였다. 이 중에서 고추 유전자지도 내 위치를 고려하여 145개의 SNP(HRM) 분석용 프라이머를 디자인하였으며, 그 중 116개가 성공적으로 다형성을 보여 유전자지도 작성에 사용되었다. 총 연관거리는 1,167.9cM였고, 연관군 수는 고추의 기본염색체 수와 일치하는 12개였다. 결과적으로 본 연구에서 제시된 방법은 시간적인 효율성과 예측의 정확성 면에서 새로운 고추 유전자지도 작성에 매우 적합함은 물론 작성된 유전자지도는 양친에서 차이를 보이는 특정 형질에 대한 QTL 분석을 하는데 바로 사용될 수 있을 것으로 판단되었다.